Low dNTP levels are necessary but may not be sufficient for lentiviral restriction by SAMHD1 - Welbourn, Sarah (Virology, 2015)
SAMHD1 is a cellular dNTPase that restricts lentiviral infection presumably by lowering cellular dNTP levels to below a critical threshold required for reverse transcription; however, lowering cellular dNTP levels may not be the sole mechanism of restriction. In particular, an exonuclease activity of SAMHD1 was reported to contribute to virus restriction. We further investigated the requirements for SAMHD1 restriction activity in both differentiated U937 and cycling HeLa cells. Using hydroxyurea treatment to lower baseline dNTP levels in HeLa cells, we were able to document efficient SAMHD1 restriction without significant further reduction in dNTP levels by SAMHD1. These results argue against a requirement for additional myeloid-specific host factors for SAMHD1 function but further support the notion that SAMHD1 possesses an additional dNTP-independent function contributing to lentiviral restriction. However, our own experiments failed to associate this presumed additional SAMHD1 antiviral activity with a reported nuclease activity.